2022
DOI: 10.1080/21655979.2022.2037227
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine attenuates apoptosis in early brain injury after subarachnoid hemorrhage through Notch1/ASK1/p38 MAPK signaling pathway

Abstract: Subarachnoid hemorrhage (SAH) is a severe brain condition associated with a significantly high incidence and mortality. As a consequence of SAH, early brain injury (EBI) may contribute to poor SAH patient outcomes. Apoptosis is a signaling pathway contributing to post-SAH early brain injury and the diagnosis of the disease. Fluoxetine is a well-studied serotonin selective reuptake inhibitor (SSRI). However, its role in apoptosis has not been clearly understood. The present investigation assessed the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Similarly, Gao et al also reported that the early overexpression of PDK4 after SAH has the potential to attenuate neuronal apoptosis by reducing oxidative stress via the ROS/ASK1/P38 pathway ( Gao X. et al, 2022 ). A recent study also demonstrated that early fluoxetine administration can protect against apoptosis by regulating the Notch1/ASK1/p38 MAPK signaling pathway, thereby ameliorating EBI after SAH ( Liu M. et al, 2022 ). Neuronal apoptosis caused by SAH is widely and thoroughly studied, involving many signaling pathways and molecular mechanisms.…”
Section: Neuronal Apoptosismentioning
confidence: 99%
“…Similarly, Gao et al also reported that the early overexpression of PDK4 after SAH has the potential to attenuate neuronal apoptosis by reducing oxidative stress via the ROS/ASK1/P38 pathway ( Gao X. et al, 2022 ). A recent study also demonstrated that early fluoxetine administration can protect against apoptosis by regulating the Notch1/ASK1/p38 MAPK signaling pathway, thereby ameliorating EBI after SAH ( Liu M. et al, 2022 ). Neuronal apoptosis caused by SAH is widely and thoroughly studied, involving many signaling pathways and molecular mechanisms.…”
Section: Neuronal Apoptosismentioning
confidence: 99%